ANALYSIS OF MICROPLASTIC CONTAMINATION ON WATER AND SEDIMENT IN THE BRANTAS SUBWATERSHED OF THE MALANG AREA - Buwono, Nanik Retno; Samuel, Pratama Diffi; Gifari, Ahmad Wahyu (Universitas Mataram, 2025)
Microplastics are non-degradable contaminants that have been found in many river waters. Microplastics not only pollute water bodies but also become pollutants in river sediments. The Malang area is one of the areas passed by the Brantas River, which is the longest river in East Java and plays an important role for the community. The Brantas River has experienced a decline in water quality related to microplastic contamination. This study aims to analyze the types of microplastics and the abundance of microplastics found in water and sediment in the Brantas Subwatershed Malang Region. This study used a survey method and determined the sampling location point by purposive sampling. Microplastics found in water and sediment samples have the same 3 types, namely fragments, fibers and films. The fragment type was found to dominate in water samples by 38.62% and also in sediment samples by 76.13%. The abundance of microplastics in water was highest at Station 5 at 686.67 particles/m3 and lowest at Station 1 at 396.67 particles/m3. While the abundance of microplastics in the sediment was highest at Station 3 at 2,517.15 particles/kg and lowest at Station 2 at 1,779.93 particles/kg.